Answer:
End-to-end delay = L/R1 + L/R2
Step-by-step explanation:
If we ignore propagation delay and processing delay (too small to be considered) and because the switch uses store-and-forward packet switching the time a packet will take from source to destination is the time the packet will take from source to switch (t1) plus the time the packet will take from switch to source (t2).
The time can be calculated using the equation: time equal length over transition rate -> t = L/R
t = t1 + t12
t = L/R1 + L/R2